2016
DOI: 10.1159/000484557
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Hebrew Version of the Eating Assessment Tool-10 (H-EAT-10)

Abstract: Background and Objectives: Dysphagia is a common disability with different etiologies. In order to measure dysphagia symptom severity and effects on quality of life, the Eating Assessment Tool (EAT-10) was developed and validated in the English language. We aimed to develop a Hebrew version of the EAT-10 and to evaluate its internal consistency, test-retest reliability, and validity in Hebrew-speaking adults with dysphagia. Subjects and Methods: The Hebrew EAT-10 (H-EAT-10) questionnaire was completed by 132 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…The Cronbach’s alpha value (0.95) was excellent for the total F-EAT-10 score in controls and FEES patients together and was also good for FEES patients alone (0.84), indicating an excellent to good internal consistency. According to the previous validations, Cronbach’s alpha for the total EAT-10 score varied from 0.87 (Sp-EAT-10) to 0.96 (the original EAT-10 of Belafsky), suggesting that our result is consistent with these previous studies [ 13 19 , 22 , 35 ]. The ICC indicating test–retest reliability was 0.93 (0.91–0.95) for both controls and FEES patients together and 0.84 (0.76–0.89) for FEES patients alone, indicating excellent to good reproducibility.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The Cronbach’s alpha value (0.95) was excellent for the total F-EAT-10 score in controls and FEES patients together and was also good for FEES patients alone (0.84), indicating an excellent to good internal consistency. According to the previous validations, Cronbach’s alpha for the total EAT-10 score varied from 0.87 (Sp-EAT-10) to 0.96 (the original EAT-10 of Belafsky), suggesting that our result is consistent with these previous studies [ 13 19 , 22 , 35 ]. The ICC indicating test–retest reliability was 0.93 (0.91–0.95) for both controls and FEES patients together and 0.84 (0.76–0.89) for FEES patients alone, indicating excellent to good reproducibility.…”
Section: Discussionsupporting
confidence: 91%
“…Although some patients reported symptom changes, some FEES patients did not answer this question and, we cannot exclude the possibility that their symptoms might also have changed. This is a probable explanation for why our test–retest results did not reach as high ICCs and correlations as observed in other studies [ 15 , 18 , 35 ].…”
Section: Discussionsupporting
confidence: 55%
“…EAT-10 also has good psychometric properties and reliability [11,[43][44][45]64]; however, Cordier et al [64] conducted Rasch analysis on EAT-10 and found that it has significant weaknesses in construction validity, including item redundancy, the lack of easy and difficult items, and different thresholds of rating scale categories. The second question ("My swallowing problem interferes with my ability to go out for meals") is difficult to answer for some patients who have been hospitalized for a long time due to diseases and only present or are diagnosed with dysphagia during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Each item corresponds to 5 levels of difficulty from "no problem" to "serious problem," with a total score of 0 to 40. EAT-10 has good internal consistency and intraclass correlation coefficients (ICCs) [11,34,36,37,39,40,[42][43][44][45][46][47]. It has been proven to be useful in screening dysphagia in the oropharyngeal and esophageal phases [11,44] and for swallowing disorders in a healthy population.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it should be emphasized that this high value was obtained from half of the EAT10 ® items of the questionnaire. Adaptations in other languages show varying degrees of test–retest reliability ranging from r = 0.73 to r = 0.98 [ 17 , 22 , 31 ]. We hypothesize that such variability may be due to inconsistencies in the implementation of test–retest, especially the different times between the test and the retest, different groups of participants (control group vs. dysphagic group), and the cultural differences themselves.…”
Section: Discussionmentioning
confidence: 99%